INTERLINGUAL CORRESPONDENCE AS A FACTOR IN ENRICHING PHRASEOLOGY AND IDENTIFYING ISOMORPHISM AND ALLOMORPHISM OF LANGUAGES (Scientific journal of the Fergana State University, 2025)
This article examines the impact of mass informatization and globalization on language contact, focusing on the derivation and borrowing of phraseological units in English, Russian, and Uzbek. It explores the isomorphic and allomorphic properties of phraseological units, analyzing their semantic, structural, and cultural dimensions. Drawing on examples from media discourse, the study highlights the role of cultural adaptation and translation strategies in preserving or transforming meaning across languages. A classification of media phraseological units into traditional, traditional-rethought, computer, and media-specific categories is proposed, reflecting the evolving nature of phraseology in response to technological advancements and the influence of the Internet. The findings reveal that phraseological units are deeply intertwined with cultural concepts, emphasizing their importance in intercultural communication and linguistic analysis. This research provides valuable insights into the pragmalinguistic properties of phraseological units and their relevance in multilingual and multicultural contexts.